A flexible memory with low-voltage and high-operation speed using an Al2O3/poly(α-methylstyrene) gate stack on a muscovite substrate. Issue 7 (23rd January 2019) - He, Huixin; He, Waner; Mai, Jiaying; Wang, Jiali; Zou, Zhengmiao; Wang, Dao; Feng, Jiajun; Zhang, Aihua; Fan, Zhen; Wu, Sujuan; Zeng, Min; Gao, Jinwei; et al.
Abstract : A clear technical demonstration of the critical role of the blocking layers, which has never been addressed sufficiently in previous work. Abstract : Flexible organic field effect transistors (OFETs) are a promising class of flexible nonvolatile memories. However, fabrication of flexible OFET devices that offer low-voltage and high-speed operation remains a challenge. Here, we report a flexible OFET memory unit based on a novel gate stack consisting of pentacene as a semiconducting channel, poly(α-methylstyrene) as a charge-trapping layer, and amorphous Al2 O3 as a charge-blocking layer, deposited sequentially on an Au-coated flexible muscovite substrate. The optimized flexible OFET structure has excellent electrical performance and mechanical flexibility, with an operating voltage as low as −4 V, an operating speed as fast as 100 μs, the largest memory window (1.73 V) provided +6 V, 100 μs program and −4 V, 100 μs erase pulses, a retention time far longer than 10 4 s, and program–erase endurance greatly exceeding 3000 cycles. The device can endure at least 5000 bending–unbending cycles. Of all flexible OFET nonvolatile memories reported to date, this OFET device offers the best overall electrical and mechanical properties and is extremely promising for future applications in flexible, lightweight, low-power, and high-speed nonvolatile memories.